A fundamental study on selective extraction of Li+ with dibenzo-14-crown-4 ether: Toward new technology development for lithium recovery from brines. (15th May 2022) - Xiong, Yanhang; Ge, Tao; Xu, Liang; Wang, Ling; He, Jindong; Zhou, Xiaowei; Tian, Yongpan; Zhao, Zhuo
Abstract: The present study has proposed a selective Li + extraction process using a novel extractant of dibenzo-14-crown-4 ether functionalized with an alkyl C16 chain (DB14C4–C16) synthesized based on the ion imprinting technology (IIT). Theoretical analysis of the possible complexes formed by DB14C4–C16 with Li + and the competing ions of Na +, K +, Ca 2+ and Mg 2+ was performed through density functional theory (DFT) modeling. The Gibbs free energy change of the complexes of metal ions with DB14C4–C16 and water molecules were calculated to be −125.81 and −166.01 kJ/mol for lithium, −55.73 and −117.77 kJ/mol for sodium, and −196.02 and −291.52 kJ/mol for magnesium, respectively. Furthermore, the solvent extraction experiments were carried out in both single Li + and multi-ions containing solutions, and the results delivered a good selectivity of DB14C4–C16 towards Li + over the competing ions, showing separation coefficients of 68.09 for Ca 2+ -Li +, 24.53 for K + -Li +, 16.32 for Na + -Li +, and 3.99 for Mg 2+ -Li + under the optimal conditions. The experimental results are generally in agreement with the theoretical calculations. Graphical abstract: Image 1 Highlights: A lithium-selective extractant was synthesized based on ion imprinting technology. The properties of various DB14C4–C16 based complexes were theoretically evaluated. Extraction experiments in single Li + and multi-ion solutions were conducted. The mechanism of complexation between DB14C4–C16 and Li + was clarified. An efficient Li  +  extraction system was developed based on supramolecular chemistry.